The SWOW-SL project - Špela Vintar; Mojca Brglez; Ela Novak; Simon De Deyne (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave)
We describe the construction of the first comprehensive collection of free word association data for Slovene. SWOW-SL was created as part of the multilingual Small World of Words project, thus relying on its methodology and data collection platform. Here we first present the cue selection process and the adaptation of the experiment for Slovene, and then the data collection campaign within which the participants were mobilized via social media and through physical advertising consisting of posters and stickers. An analysis of various campaign strategies is provided, giving valuable insight for future crowdsourcing projects. The result is the first association data set for Slovene comprising 1,000 cue words and a total of 20,000 responses. The data set is released on the Clarin.si repository and opens up a range of new possibilities for research in cognitive linguistics, natural language processing and related fields.